Concentration dependent interfacial chemistry of the NaOH(aq): gibbsite interface. Issue 35 (24th August 2022) - Liu, Wei; Pouvreau, Maxime; Stack, Andrew G.; Yang, Xiaoning; Clark, Aurora E.
Abstract : Caustic conditions are often employed for dissolution of a wide variety of minerals, where ion sorption, surface diffusion, and interfacial organization impact surface reactivity. Abstract : Caustic conditions are often employed for dissolution of a wide variety of minerals, where ion sorption, surface diffusion, and interfacial organization impact surface reactivity. In the case of gibbsite, γ-Al(OH)3, the chemistry at the NaOH(aq) interface is deeply intertwined with industrial processing of aluminum, including metal production and the disposition of Al-containing wastes. To date, little is known about the structure, speciation, and dynamic behavior of gibbsite interfaces (and that of many other minerals) with NaOH(aq) —particularly as a function of ionic strength. Yet concentration-dependent interfacial organization and dynamics are a critical starting point to develop a fundamental understanding of the factors that influence dissolution. This work reports equilibrium molecular dynamics simulations of the γ-Al(OH)3 :NaOH(aq) interface, revealing the sorption behavior and speciation of ions from 0.5–10 M [NaOH]. As inner-sphere complexes, Na + primarily coordinates to the side of the gibbsite hexagonal cavities, while OH − accepts hydrogen-bonding from the surface-OH groups. The mobility of inner-sphere Na + and OH − ions is significantly reduced due to a strong surface affinity in comparison to previous reports of NaCl, CaCl2, or BaCl2 electrolytes. At high [NaOH], contact ion pairing that is observed in the bulk solution is partially disrupted upon sorption to the gibbsite surface by the individual ion–surface interactions. The molecular-scale changes to surface speciation and competition between ion–surface vs. ion–ion interactions influence surface characterization of gibbsite and potential dissolution processes, providing a valuable baseline for starting conditions needed within future reactive molecular simulations.